LOCAL ELECTION AND THE FUTURE OF INDONESIAN DEMOCRACY - Ibrahim, . (PEOPLE: International Journal of Social Sciences, 2017)
This writing is basically a critical reflection on local democracy phenomenon in Indonesia that has become the barometer for democracy in national level. By qualitative approach that implemented data collection technique in the form of interview, observation, and documentation, this writing telescoped democracy phenomenon in local level. Political party domination and centralization, identity contestation, money politic phenomenon, pragmatic voter emergence, senior politician domination along with regeneration crisis, and bias gender politics were the important findings in terms of the new issues in local election that were identified by writer. Finally, this writing concluded that local democracy direction in Indonesia had not included into democracy consolidation phase considering that many new problems had not showed any sign to stop. If that is the case, then Indonesian democracy face will remain under the fragility shadows. Therefore, it still needs to wait for the test period of Indonesian democracy power.